FOREIGN LANGUAGE LEARNING METHOD AND CHARACTER BUILDING IN JAPAN - Tomoya Mitsumoto (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
The numbers of students continue to higher education in Indonesia in 10 years showed a 2-fold increase. In 2004, the number is about 17%, and 2014 it increases into 32%. The increasing in the quantity continues to higher education is good, however, at this time the quality is very important. The education quality is the quality of learning, how to teach, and on top of it is how to learn.